2016
DOI: 10.5194/acp-16-4725-2016
|View full text |Cite
|
Sign up to set email alerts
|

Long-range transport and mixing of aerosol sources during the 2013 North American biomass burning episode: analysis of multiple lidar observations in the western Mediterranean basin

Abstract: Abstract. Long-range transport of biomass burning (BB) aerosols between North America and the Mediterranean region took place in June 2013. A large number of groundbased and airborne lidar measurements were deployed in the western Mediterranean during the Chemistry-AeRosol Mediterranean EXperiment (ChArMEx) intensive observation period. A detailed analysis of the potential North American aerosol sources is conducted including the assessment of their transport to Europe using forward simulations of the FLEXPART… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…The summer of 2013 was one of the driest in the previous decades in the USA and Canada. Large forest fires caused by thunderstorms started at the end of June 2013 and continued being active during July and August, causing vast forest areas to burn up (Ancellet et al, 2016). In a previous work (Ortiz-Amezcua et al, 2014), a preliminary optical description was given for the lidar detection of a smoke event over Granada (Spain) in July 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summer of 2013 was one of the driest in the previous decades in the USA and Canada. Large forest fires caused by thunderstorms started at the end of June 2013 and continued being active during July and August, causing vast forest areas to burn up (Ancellet et al, 2016). In a previous work (Ortiz-Amezcua et al, 2014), a preliminary optical description was given for the lidar detection of a smoke event over Granada (Spain) in July 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Markowicz et al (2016) used in situ measurements, passive and active remote sensing observations and numerical simulations to describe the temporal variability of aerosol optical properties for the same period over Poland, and Janicka et al (2016) studied the properties of the mixing of those smoke particles with dust particles over Warsaw. Ancellet et al (2016) reported optical properties of the smoke plumes transported over some stations in the western Mediterranean Basin in June 2013. Veselovskii et al (2015) described vertically resolved optical and microphysical properties of particles detected in Washington, DC coming from similar forest fires after regional transport in August 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have 60 already reported transatlantic transport of boreal forests fire emissions from North America to Central Europe Petzold et al, 2007) or to the MB (Formenti et al, 2002;Cristofanelli et al, 2013;Ancellet et al, 2016). Those studies were mainly focused on biomass burning aerosols except that of Forster et al (2001) which also addressed CO emissions, but with measurements made in Germany, thus, concerning Central Europe.…”
Section: Within This Scientific Framework Chemistry-aerosol Mediterrmentioning
confidence: 99%
“…Over the MB, Formenti et al (2002) have found a forest fire haze layer up to 3.5 km coming from Canadian forest fires over the eastern Mediterranean. Ancellet et al (2016) have reported aerosol layers up to 7 km coming from North America over the western MB. The published cases we know of transatlantic transport to MB in the recent years are gathered in North America.…”
mentioning
confidence: 99%
See 1 more Smart Citation